The novel ghrelin receptor inverse agonist PF-5190457 administered with alcohol: preclinical safety experiments and a phase 1b human laboratory study - Lee, Mary R. (Mol Psychiatry, 2018)
Rodent studies indicate that ghrelin receptor blockade reduces alcohol consumption. However, no ghrelin receptor blockers have been administered to heavy drinking individuals. Therefore, we evaluated the safety, tolerability, pharmacokinetics (PK), pharmacodynamics (PD) and behavioral effects of a novel ghrelin receptor inverse agonist, PF-5190457, when co-administered with alcohol. We tested the effects of PF-5190457 combined with alcohol on locomotor activity, loss-of-righting reflex (a measure of sedative alcohol actions), and on blood PF-5190457 concentrations in rats. Then, we performed a single-blind, placebo-controlled, within-subject human study with PF-5190457 (placebo/0mg b.i.d., 50mg b.i.d., 100mg b.i.d.). Twelve heavy drinkers during three identical visits completed an alcohol administration session, subjective assessments, an alcohol cue-reactivity procedure, and gave blood samples for PK/PD testing. In rats, PF-5190457 did not interact with the effects of alcohol on locomotor activity or loss of righting reflex. Alcohol did not affect blood PF-5190457 concentrations. In humans, all adverse events were mild or moderate and did not require discontinuation or dose reductions. Drug dose did not alter alcohol concentration or elimination, alcohol-induced stimulation or sedation, or mood during alcohol administration. Potential PD markers of PF-5190457 were acyl-to-total ghrelin ratio and insulin growth factor-1. PF-5190457 (100 mg b.i.d.) reduced alcohol craving during the cue-reactivity procedure. This study provides the first translational evidence of safety and tolerability of the ghrelin receptor inverse agonist PF-5190457 when co-administered with alcohol. PK/PD/behavioral findings support continued research of PF-5190457 as a potential pharmacological agent to treat alcohol use disorder.